Influence of crystal phase on TiO2 nanowire anodes in sodium ion batteries. Issue 37 (14th September 2017) - Liu, Yi; Zhao, Feipeng; Li, Jitao; Li, Yanguang; McLeod, John A.; Liu, Lijia
Abstract : We elucidate the differences in sodium storage mechanism of TiO2 (B) and anatase TiO2 nanowires as anodes in sodium ion batteries. Abstract : Nanostructured TiO2 is a promising anode material for Na-ion batteries. In this work, we present a comparative study of anatase and B-phase TiO2 nanowires used for this purpose. We employ X-ray absorption spectroscopy and density functional theory in addition to standard characterization methods to reveal that Na is inserted into both anatase and B-phase nanowires, and that the reversible (de)sodiation capacity is almost the same for both. However the long-term stability of anatase-based Na-ion batteries is poorer than B-phase-based Na-ion batteries. We propose this is due to the irreversible formation of Na x TiO2 near the surface, which blocks Na diffusion. Improved Na-ion battery performance may therefore be obtained using TiO2 (B) anodes and by choosing nanostructure geometries with rough surfaces, limiting the unwanted blocking ability of surface barrier layers.